Intergovernmental Transfer Dynamics in Indonesia’s Fiscal Decentralization: Evidence from a Punctuated Equilibrium Perspective - Farisa Noviyanti (JURNAL MANAJEMEN KEUANGAN PUBLIK, 2026)
This study examined the dynamics of fiscal decentralization reform in Indonesia using the framework of Punctuated Equilibrium Theory (PET). Since the early 2000s, intergovernmental transfers have expanded steadily and have become the primary source of subnational government revenue. However, the COVID-19 pandemic and the enactment of Law No. 1 of 2022 on Central–Regional Financial Relations marked an important institutional shift in Indonesia’s fiscal governance. This research analyzed annual intergovernmental transfer allocations from 2001 to 2025 obtained from official State Budget data. The study applies distributional analysis of annual growth rates and complemented the quantitative assessment with qualitative policy document review. The results indicated that changes in transfer allocations followed a leptokurtic distribution, characterized by many small incremental adjustments and a limited number of large fiscal shifts. The period after 2020 showed a clear deviation from the previous expansionary pattern, suggesting the occurrence of a fiscal punctuation triggered by economic shock and regulatory reform. These findings indicated that Indonesia’s fiscal decentralization trajectory reflected prolonged periods of incremental stability interrupted by episodic structural adjustments. The study contributes to the literature on public finance and policy dynamics by demonstrating how institutional structure and crisis events interact in shaping fiscal decentralization reform in developing countries.